Выращивание монокристаллов алмаза типа Па в ростовых системах на основе Mg–C - Коваленко, Т.В.; Заневский, О.А.; Белявина, Н.Н.; Ивахненко, С.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The results of researches on growing of IIa type diamond monocrystals in growth systems on the basis of Mg–C by a method of a temperature gradient at a variation of structure of solvent are presented.